SecuCheck: Engineering configurable taint analysis for software developers - Piskachev, Goran; Krishnamurthy, Ranjith; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

IDE Support for Cloud-Based Static Analyses - Luo, Linghui; Schäf, Martin; Sanchez, Daniel; Bodden, Eric (Proceedings of the 29th ACM Joint Meeting on European Software Engineering Conference and Symposium on the Foundations of Software Engineering)

SootFX: A Static Code Feature Extraction Tool for Java and Android - Karakaya, Kadiray; Bodden, Eric (2021 IEEE 21st International Working Conference on Source Code Analysis and Manipulation (SCAM))

Integrated superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides - Höpker, Jan Philipp; Verma, Varun B; Protte, Maximilian; Ricken, Raimund; Quiring, Viktor; Eigner, Christof; Ebers, Lena; Hammer, Manfred; Förstner, Jens; Silberhorn, Christine; Mirin, Richard P; Woo Nam, Sae; et al. (Journal of Physics: Photonics)
We demonstrate the integration of amorphous tungsten silicide superconducting nanowire single-photon detectors on titanium in-diffused lithium niobate waveguides. We show proof-of-principle detection of evanescently coupled photons of 1550 nm wavelength using bidirectional waveguide coupling for two orthogonal polarization directions. We investigate the internal detection efficiency as well as detector absorption using coupling-independent characterization measurements. Furthermore, we describe strategies to improve the yield and efficiency of these devices.

Gesellschaftliche Transformationen durch die Steigerung (popmusik)kultureller Teil-habe mittels innovativer Preiskonzepte – ein interdisziplinärer Literaturüberblick - Müller, Stefanie Jutta Marianne; Kundisch, Dennis

A Generalized Stress State and Temperature Dependent Damage Indicator Framework for Ductile Failure Prediction in Heat-Assisted Forming Operations - Camberg, Alan Adam; Erhart, Tobias; Tröster, Thomas (Materials)
Heat-assisted forming processes are becoming increasingly important in the manufacturing of sheet metal parts for body-in-white applications. However, the non-isothermal nature of these processes leads to challenges in evaluating the forming limits, since established methods such as Forming Limit Curves (FLCs) only allow the assessment of critical forming strains for steady temperatures. For this reason, a temperature-dependent extension of the well-established GISSMO (Generalized Incremental Stress State Dependent Damage Model) fracture indicator framework is developed by the authors to predict forming failures under non-isothermal conditions. In this paper, a general approach to combine several isothermal FLCs within the temperature-extended GISSMO model into a temperature-dependent forming limit surface is investigated. The general capabilities of the model are tested in a coupled thermo-mechanical FEA using the example of warm forming of an AA5182-O sheet metal cross-die cup. The obtained results are then compared with state of the art of evaluation methods. By taking the strain and temperature path into account, GISSMO predicts greater drawing depths by up to 20% than established methods. In this way the forming and so the lightweight potential of sheet metal parts can by fully exploited. Moreover, the risk and locus of failure can be evaluated directly on the part geometry by a contour plot. An additional advantage of the GISSMO model is the applicability for low triaxialities as well as the possibility to predict the materials behavior beyond necking up to ductile fracture.
Keywords: General Materials Science

Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung 2020

Die Landstraße jenseits der Bedeutung. Peter Handkes spätes Drama Die Unschuldigen, ich und die Unbekannte am Rand der Landstraße - Famula, Marta (Literatur und Kultur zwischen West und Ost. Imagination, Kommunikation und Wahrnehmung in regionalen Kulturräumen. Festschrift für Paul Martin Langner zum 65. Geburtstag)

Von der auf den Kopf gestellten Schönheit oder die Verneinung der Negation im Hässlichen. Zur dialektischen Funktion des Erhabenen und des Hässlichen bei Christian Hermann Weiße - Famula, Marta (Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung)

Vom Entschluss, die Welt zu bestehen. Dürrenmatts Ethik des ‚à la bande‘ - Famula, Marta (Kosmos Dürrenmatt. Eine Annäherung an den Denker, Dichter und Maler. Berner Zeitschrift für Geschichte, H. 3. Sonderdruck Spiezer Tagung, in: Annelise Hüssy, Stefanie Leuenberger (Hgg.))

Ästhetik im Vormärz – Zur Einführung - Famula, Marta; Otto Eke, Norbert (Ästhetik im Vormärz. Jahrbuch Forum Vormärz Forschung 2020)

Lukas Bärfuss: Malinois. Erzählungen. Wallstein: Göttingen 2019 - Famula, Marta (Jahrbuch für internationale Germanistik, Jahrgang LIII – Heft 1 (2021))

Folklinguistic perceptions of Global Englishes among German learners of English - Meer, Philipp; Hartmann, Johanna; Rumlich, Dominik (European Journal of Applied Linguistics)

Das Unveränderliche und die Wiederholung. Die Rolle der Kontingenz in Max Frischs letztem Drama Triptychon - Famula, Marta (Wiederholung im Theater. Zur deutschsprachigen Gegenwartsdramatik und ihrer Inszenierung, (= Gesellschaftskritische Literatur – Texte Autoren – Debatten 9))

Drama zwischen Text und Bühne (Schriftenreihe seit 2021)

A Multi-Model-Particle Filtering-Based Prognostic Approach to Consider Uncertainties in RUL Predictions - Bender, Amelie (Machines)
While increasing digitalization enables multiple advantages for a reliable operation of technical systems, a remaining challenge in the context of condition monitoring is seen in suitable consideration of uncertainties affecting the monitored system. Therefore, a suitable prognostic approach to predict the remaining useful lifetime of complex technical systems is required. To handle different kinds of uncertainties, a novel Multi-Model-Particle Filtering-based prognostic approach is developed and evaluated by the use case of rubber-metal-elements. These elements are maintained preventively due to the strong influence of uncertainties on their behavior. In this paper, two measurement quantities are compared concerning their ability to establish a prediction of the remaining useful lifetime of the monitored elements and the influence of present uncertainties. Based on three performance indices, the results are evaluated. A comparison with predictions of a classical Particle Filter underlines the superiority of the developed Multi-Model-Particle Filter. Finally, the value of the developed method for enabling condition monitoring of technical systems related to uncertainties is given exemplary by a comparison between the preventive and the predictive maintenance strategy for the use case.
Keywords: prognostics; RUL predictions; particle filter; uncertainty consideration; Multi-Model-Particle Filter; model-based approach; rubber-metal-elements; predictive maintenance

Computed tomography investigation of the material structure in clinch joints in aluminium fibre-reinforced thermoplastic sheets - Gröger, B.; Köhler, D.; Vorderbrüggen, J.; Troschitz, J.; Kupfer, R.; Meschut, G.; Gude, M. (Production Engineering)

Holistic investigation chain for the experimental determination of fracture mechanical material parameters with special specimens - Weiß, D.; Schramm, B.; Kullmer, G. (Production Engineering)

Approach for the automated and data-based design of mechanical joints - Zirngibl, C.; Schleich, B.; Wartzack, S. (Proceedings of the Design Society)

Application of reinforcement learning for the optimization of clinch joint characteristics - Zirngibl, C.; Dworschak, F.; Schleich, B.; Wartzack, S. (Production Engineering)

Joining of CFRT-steel hybrid parts via hole-forming and subsequent pin caulking - Römisch, D.; Popp, J.; Drummer, D.; Merklein, M. (Production Engineering)

A New Non-destructive Testing Method Applied to Clinching - Lafarge, R.; Wolf, A.; Guilleaume, C.; Brosius, A. (Minerals, Metals and Materials Series)

Experimental study on joining by forming of hct590x + z and en-aw 6014 sheets using cold extruded pin structures - Römisch, D.; Kraus, M.; Merklein, M. (Journal of Manufacturing and Materials Processing)
Due to stricter emission targets in the mobility sector and the resulting trend towards lightweight construction in order to reduce weight and consequently emissions, multi-material systems that allow a material to be placed in the right quantity and in the right place are becoming increasingly important. One major challenge that is holding back the rapid and widespread use of multi-material systems is the lack of adequate joining processes that are suitable for joining dissimilar materials. Joining processes without auxiliary elements have the advantage of a reduced assembly effort and no additional added weight. Conventional joining processes without auxiliary elements, such as welding, clinching, or the use of adhesives, reach their limits due to different mechanical properties and chemical incompatibilities. A process with potential in the field of joining dissimilar materials is joining without an auxiliary element using pin structures. However, current pin manufacturing processes are mostly time-consuming or can only be integrated barely into existing industrial manufacturing processes due to their specific properties. For this reason, the present work investigates the production of single- and multi-pin structures from high-strength dual-phase steel HCT590X + Z (DP600, t0 = 1.5 mm) by cold extrusion directly out of the sheet metal. These structures are subsequently joined with an aluminium sheet (EN AW-6014-T4, t0 = 1.5 mm) by direct pin pressing. For a quantitative evaluation of the joint quality, tensile shear tests are carried out and the influence of different pin heights, pin number, and pin arrangements, as well as different joining strategies on the joint strength is experimentally evaluated. It is proven that a single pin structure with a diameter of 1.5 mm and an average height of 1.86 mm achieves a maximum tensile shear force of 1025 N. The results reveal that the formation of a form-fit during direct pin pressing is essential for the joint strength. By increasing the number of pins, a linear increase in force could be demonstrated, which is independent of the arrangement of the pin structures.

Investigation of Different Joining by Forming Strategies when Connecting Different Metals without Auxiliary Elements - Römisch, D.; Kraus, M.; Merklein, M. (Key Engineering Materials)
Lightweight constructions become more and more important, especially in the mobility sector. In this industry, the increasingly strict regulations regarding the emissions of carbon dioxide can be achieved to a certain extent by reducing the vehicle weight. Thus, multi-material systems are used. Conventional joining techniques reach their limits when joining different materials due to different thermal expansion, unequal stiffness or chemical incompatibilities. This is why additional joining elements or adhesives are used. These must be viewed critically regarding a lightweight and resource-efficient production, since they add weight or complicate the recycling process of these components. Consequently, there is a great and growing need for new versatile joining technologies in order to overcome these challenges and to be able to react to changing process parameters and boundary conditions. Joining without an auxiliary element using pin structures formed directly from the sheet metal plane is one approach to meet these challenges. These pin structures are then joined by direct pressing into the joining partner. This is possible with a variety of material combinations, but is advantageous with regard to continuous fibre-reinforced thermoplastic composites (CFRTP), as the fibres do not have to be cut when joining CFRTP using pin structures. In this paper, the formability of pin structures made of a dual-phase steel DP600 (HCT590X + Z) is investigated. The extruded pin structures are joined by direct pin pressing with an EN AW-6014 to form tensile shear specimens. Different joining strategies are investigated to compare their influence on the joint strength. The results have shown that it is feasible to form suitable pins from a DP600 dual-phase steel to produce reliable connections with an aluminium sheet joined by direct pin pressing.

Material characterisation methods for a tumbling self-piercing riveting process - Wituschek, S.; Lechner, M. (ESAFORM 2021)
The growing demands of resource-saving processes and products are leading to increasing importance of lightweight construction for the automotive industry. One approach is multi-material design, which uses high-strength steels and aluminium alloys in the production of vehicle bodies. Therefore, reliable processes for joining components with different mechanical properties and geometries are necessary. As conventional joining processes reach their limits, new versatile processes and methods are required which can adapt to different process conditions and disturbance variables. A widely used joining process to join different materials is self-piercing riveting as a joining by forming method, however it is characterised as inflexible to changing process conditions due to a linear process kinematic and rigid dies. An approach to extend the process limits is the application of a tumbling kinematic for the punch. Thus, an adapted tumbling strategy can be used to influence the joining process and to achieve a controlled material flow in order to manufacture tailored joints. For the fundamental investigation of the process, numerical investigations are necessary. In order to achieve high model quality a precise material modelling is crucial. Therefore, a characterisation of the materials HCT590X+Z and EN AW-6014 as typical materials of multi-material mixes and the rivet material 38B2 is performed. Due to the different stress conditions during tumbling self-piercing riveting suitable characterisation methods are selected and carried out.

A Method for Characterization of Geometric Deviations in Clinch Points with Computed Tomography and Transient Dynamic Analysis - Köhler, D.; Sadeghian, B.; Kupfer, R.; Troschitz, J.; Gude, M.; Brosius, A. (Key Engineering Materials)
When joining lightweight parts of various materials, clinching is a cost efficient solution. In a production line, the quality of a clinch point is primarily controlled by measurement of dimensions, which are accessible from outside. However, methods such as visual testing and measuring the bottom thickness as well as the outer diameter are not able to deliver any information about the most significant geometrical characteristic of the clinch point, neck thickness and undercut. Furthermore, ex-situ destructive methods such as microsectioning cannot detect elastic deformations and cracks that close after unloading. In order to exceed the current limits, a new non-destructive in-situ testing method for the clinching process is necessary. This work proposes a concept to characterize clinch points in-situ by combining two complementary non-destructive methods, namely, computed tomography (CT) and ultrasonic testing. Firstly, clinch points with different geometrical characteristics are analysed experimentally using ex-situ CT to get a highly spatially resolved 3D-image of the object. In this context, highly X-ray attenuating materials enhancing the visibility of the sheet-sheet interface are investigated. Secondly, the test specimens are modelled using finite element method (FEM) and a transient dynamic analysis (TDA) is conducted to study the effect of the geometrical differences on the deformation energy and to qualify the TDA as a fast in-situ non-destructive method for characterizing clinch points at high temporal resolution.

Effect of Different Tool Geometries on the Mechanical Properties of Al-Al Clinch Joints - Ewenz, L.; Kalich, J.; Zimmermann, M.; Füssel, U. (Key Engineering Materials)
The use of clinch joints, e.g. vehicle structures, is determined by the reliability of the joint and its strength properties - in particular the fatigue strength. Clinch connections offer the advantage over form-closure and force-closure processes that they can also be used for hybrid material combinations. In order to be able to evaluate the influence of the geometry parameters such as e.g. undercut, neck thickness or also base thickness on the fatigue behavior, three clinch connections (in optimum and compromise design) with different tool parameters were designed and examined using the example of a joining task with aluminum sheet material. For this purpose, fatigue curves (F-N curves) in the range of high to very high numbers of load cycles (N = 105 to 107) were determined. In this load cycle range, a so-called "neck fracture" is mainly to be expected as the type of failure, whereas for quasi-static tests, a “buckling” is more likely to occur. The tests were carried out on single-cut overlapping shear tensile specimens. Metallographic and scanning electron microscopic examinations of the joints and the fracture surfaces served to identify the crack initiation site and to clarify the respective type of failure. Significant differences in the damage behaviour of the three clinching variants could be shown. This observation enables one step into the direction of fully understanding the relationship along the causal chain "joint requirements - joining process - fatigue strength". Thus the adaptability of the clinching process can be improved.

Modelling of thermally supported clinching of fibre-reinforced thermoplastics: Approaches on mesoscale considering large deformations and fibre failure - Gröger, B.; Hornig, A.; Hoog, A.; Gude, M. (ESAFORM 2021 - 24th International Conference on Material Forming)
Thermally supported clinching (Hotclinch) is a novel promising process to join dissimilar materials. Here, metal and fibre-reinforced thermoplastics (FRTP) are used within this single step joining process and without the usage of auxiliary parts like screws or rivets. For this purpose, heat is applied to improve the formability of the reinforced thermoplastic. This enables joining of the materials using conventional clinching-tools. Focus of this work is the modelling on mesoscopic scale for the numerical simulation of this process. The FTRP-model takes the material behaviour both of matrix and the fabric reinforced organo-sheet under process temperatures into account. For describing the experimentally observed phenomena such as large deformations, fibre failure and the interactions between matrix and fibres as well as between fibres themselves, the usage of conventional, purely Lagrangian based FEM methods is limited. Therefore, the combination of contact-models with advanced modelling approaches like Arbitrary-Lagrangian-Eulerian (ALE), Coupled-Eulerian-Lagrangian (CEL) and Smooth-ParticleHydrodynamics (SPH) for the numerical simulation of the clinching process are employed. The different approaches are compared with regard to simulation feasibility, robustness and results accuracy. It is shown, that the CEL approach represents the most promising approach to describe the clinching process.

Development of a novel adaptive joining technology employing friction-spun joint connectors (FSJC) - Wiens, E.; Wischer, C.; Homberg, W. (ESAFORM)
Joints are an essential part of modern (lightweight) structures in a broad variety of applications. The reason for this is the rapidly increasing number of different material combinations needing to be joined in application areas like the automotive industry. It is currently common to use numerous auxiliary or standardized elements instead of individually adapted joining elements. This leads to a large number of different joining elements per product and thus to high costs. An innovative approach to overcoming this issue is the design, manufacture and setting of joint-specific joining elements. A good candidate for the manufacture of adapted joining elements of this type is the so-called friction spinning process. The joining elements formed in this way can be specifically adapted to the application in question in terms of both shape and mechanical properties. The part geometry required for the properties of a given joint is formed using a universal forming tool. This makes it possible to form a wide variety of sub geometries for the auxiliary joining part as a function of the prevailing joint condition, using a single forming tool and starting from the same semi-finished bar material. By applying different process strategies for the rotational speed and feed rate during the forming operation, the same part geometry can even be given different local mechanical properties. The following contribution presents the results of ongoing research work and includes the process concept, process properties, tooling and the results of experimental investigations into the joining of two sheet metal parts with help of this new joining process.

A First Approach for the Treatment of Galvanic Corrosion and of Load-Bearing Capacity of Clinched Joints - Harzheim, S.; Steinfelder, C.; Wallmersperger, T.; Brosius, A. (Key Engineering Materials)
Corrosion is a major cause for the failure of metallic components in various branches of the industry. Depending on the corrosion severity, the time until failure of the component varies. On the contrary, a study has shown that certain riveted metal joints, exposed to a short period of mechanical loading and corrosion, have greater fatigue limits. This study gives rise to the question how different corrosion exposure times affect joint metallic components. In the present research, a theoretical approach is developed in order to evaluate the influence of galvanic corrosion on joint integrity of clinched metal joints. At first, the framework for modeling galvanic corrosion is introduced. Furthermore, a simulative investigation of a clinching point is carried out based on the assumption that corrosion leads to a reduction of the contact area which leads to a local increase in contact pressure. For this purpose, the stiffness values of individual elements in a finite element model are reduced locally in the contact area of the undercut and the contact stress along a path is evaluated. Summarizing, a modeling approach is introduced to investigate corrosion effects on load-bearing behavior of clinched joints.

A finite plasticity gradient-damage model for sheet metals during forming and clinching - Friedlein, J.; Mergheim, J.; Steinmann, P. (Key Engineering Materials)
In recent years, clinching has gathered popularity to join sheets of different materials in industrial applications. The manufacturing process has some advantages, as reduced joining time, reduced costs, and the joints show good fatigue properties. To ensure the joint strength, reliable simulations of the material behaviour accounting for process-induced damage are expected to be beneficial to obtain credible values for the ultimate joint strength and its fatigue limit. A finite plasticity gradient-damage material model is outlined to describe the plastic and damage evolutions during the forming of sheet metals, later applied to clinching. The utilised gradient-enhancement cures the damage-induced localisation by introducing a global damage variable as an additional finite element field. Both, plasticity and damage are strongly coupled, but can, due to a dual-surface approach, evolve independently. The ability of the material model to predict damage in strongly deformed sheets, its flexibility and its regularization properties are illustrated by numerical examples.

Temperature dependent modelling of fibre-reinforced thermoplastic organo-sheet material for forming and joining process simulations - Gröger, B.; Hornig, A.; Hoog, A.; Gude, M. (Key Engineering Materials)
Joining and local forming processes for fibre-reinforced thermoplastics (FRTP) like hole-forming or variations of the clinching process require an in-depth understanding of the process induced effects on meso-scale. For numerical modelling with a geometrical description of a woven fabric, adequate material models for a representative unit cell are identified. Model calibration is achieved employing a mesoscopic finite-element-approach using the embedded element method based on tensile tests of the consolidated organo-sheets and a phenomenological evaluation of photomicrographs. The model takes temperature dependent stiffness and fibre tension failure into account.

A first Model of Fatigue Corrosion of a Metal through Hydrogen Embrittlement - Hofmann, M.; Shi, Y.; Wallmersperger, T. (PAMM)
Predicting the durability of components under mechanical loading combined with environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. Precise predictions are neccesary for lightweight design in transportation due to environmental protection. During corrosion often hydrogen is produced by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions leading to early and unexpected failure. Until now predictions are mostly done through costly experiments. In the present research, a first simple simulation model based on the fundamentals of electrochemistry and continuum damage mechanics is developed to couple the damage induced by the mechanical stress with the hydrogen embrittlement. Results of the durability are presented for the case of uniaxial cyclic loading for varying testing frequency.

Approach for the automated analysis of geometrical clinch joint characteristics - Zirngibl, C.; Schleich, B. (Key Engineering Materials)
Due to their cost-efficiency and environmental friendliness, the demand of mechanical joining processes is constantly rising. However, the dimensioning and design of joints and suitable processes are mainly based on expert knowledge and few experimental data. Therefore, the performance of numerical and experimental studies enables the generation of optimized joining geometries. However, the manual evaluation of the results of such studies is often highly time-consuming. As a novel solution, image segmentation and machine learning algorithm provide methods to automate the analysis process. Motivated by this, the paper presents an approach for the automated analysis of geometrical characteristics using clinching as an example.

Parametric FEM for computational homogenization of heterogeneous materials with random voids - Pivovarov, Dmytro; Mergheim, Julia; Willner, Kai; Steinmann, Paul (PAMM)
Computational homogenization is a powerful tool which allows to obtain homogenized properties of materials on the macroscale from the simulation of the underlying microstructure. The response of the microstructure is, however, strongly affected by variations in the microstructure geometry. The effect of geometry variations is even stronger in cases when the material exhibits plastic deformations. In this work we study a model of a steel alloy with arbitrary distributed elliptic voids. We model one single unit cell of the material containing one single void. The geometry of the void is not precisely known and is modeled as a variable orientation of an ellipse. Large deformations applied to the unit cell necessitate a finite elasto-plastic material model. Since the geometry variation is parameterized, we can utilize the method recently developed for stochastic problems but also applicable to all types of parametric problems — the isoparametric stochastic local FEM (SL-FEM). It is an ideal tool for problems with only a few parameters but strongly nonlinear dependency of the displacement fields on parameters. Simulations demonstrate a strong effect of parameter variation on the plastic strains and, thus, substantiate the use of the parametric computational homogenization approach.

In situ backside Raman spectroscopy of zinc oxide nanorods in an atmospheric‐pressure dielectric barrier discharge plasma - Knust, Steffen; Ruhm, Lukas; Kuhlmann, Andreas; Meinderink, Dennis; Bürger, Julius; Lindner, Jörg; de los Arcos de Pedro, Maria Teresa; Grundmeier, Guido (Journal of Raman Spectroscopy)
Keywords: Spectroscopy; General Materials Science

Impact of lunch with carbohydrates differing in glycemic index on children's cognitive functioning in the late postprandial phase: a randomized crossover study - Drozdowska, Alina; Sinningen, Kathrin; Falkenstein, Michael; Rudolf, Henrik; Libuda, Lars; Buyken, Anette; Lücke, Thomas; Kersting, Mathilde (European Journal of Nutrition)
Abstract Purpose Studies about effects of lunch dietary Glycemic Index (GI) on cognition of schoolchildren are scarce. Our previous CogniDo GI study found no changes of cognition in the early postprandial phase after consumption of two rice types with medium vs. high dietary GI for lunch (i.e., 45 min after starting lunch). This study investigated whether the dietary GI of lunch has an impact on cognition of schoolchildren in the late postprandial phase, 90 min after lunch. Methods A randomized, 2 × 2 crossover intervention study was conducted at a comprehensive school with 5th and 6th grade students. Participants ( n = 212) were randomly assigned to either sequence 1 or 2. In the first period, participants of sequence 1 received a dish with high GI rice (GI: 79), those of sequence 2 with medium GI rice (GI: 64)—in the second period, 1 week later, vice versa. Computer-based cognitive testing was performed 90 min after lunch examining tonic alertness, visual search and task switching, and working memory. Treatment effects and treatment effects adjusted for estimated lunch glycemic load (GL) were analyzed using a linear mixed model. Results The selected cognitive parameters were not affected by the GI of lunch 90 min after lunch, neither after intention-to-treat nor in the per-protocol analysis. Adjustment for GL also did not change results. Conclusion The present study revealed no notable differences after the consumption of two rice types with medium vs. high dietary GI for lunch in children’s cognitive function in the late postprandial phase, 90 min after lunch. Clinical trial registration German Clinical Trials Register (DRKS00013597); date of registration: 16/04/2018, retrospectively registered.
Keywords: Nutrition and Dietetics; Medicine (miscellaneous)

Maturity-based Development of Strategic Thrusts for Socio-technical Risks - Menzefricke, Joern Steffen; Wiederkehr, Ingrid; Koldewey, Christian; Dumitrescu, Roman (Procedia CIRP)
Keywords: General Medicine

Digitalisation in Agriculture: Knowledge and Learning Requirements of German Dairy Farmers - Goller, Michael; Caruso, Carina; Harteis, Christian (International Journal for Research in Vocational Education and Training)
Purpose: This study aims at investigating how digitalisation (in the sense of industry 4.0) has changed the work of farmers and how they experience the changes from more traditional work to digitalised agriculture. It also investigates what knowledge farmers require on digitalised farms and how they acquire it. Dairy farming was used as domain of investigation since it, unlike other industries, has strongly been affected by digitalisation throughout the last years. Method: Exploratory interviews with 10 livestock farmers working on digitalised dairy farms were analysed using qualitative content analysis. A deductive and inductive coding strategy was used. Findings: Farming work has changed from more manual tasks towards symbol manipulation and data processing. Farmers must be able to use computers and other digital devices to retrieve and analyse sensor data that allow them to monitor and control the processes on their farm. For this new kind of work, farmers require elaborated mental models that link traditional farming knowledge with knowledge about digital systems, including a strong understanding of production processes underlying their farm. Learning is mostly based on instructions offered by manufacturers of the new technology as well as informal and non-formal learning modes. Even younger farmers report that digital technology was not sufficiently covered in their (vocational) degrees. In general, farmers emphasises the positive effects of digitalisation both on their working as well as private life. Conclusions: Farmers should be aware of the opportunities as well as the potential drawbacks of the digitalisation of work processes in agriculture. Providers of agricultural education (like vocational schools or training institutes) need to incorporate the knowledge and skills required to work in digitalised environments (e.g., data literacy) in their syllabi. Further studies are required to assess how digitalisation changes farming practices and what knowledge as well as skills linked to these developments are required in the future.
Keywords: Work-Based Learning; Organisational Change; Digital Competences; Qualitative Research; Digitalisation; Farming; Dairy; VET; Vocational Education and Training

„… damit unsere Welt eine gute Welt werden kann.“ Explorative Befunde einer Befragung von Religionslehrkräften zu ihrem professionsbezogenen Selbstverständnis - Caruso, Carina; Woppowa, Jan (Theo-Web, Zeitschrift für Religionspädagogik, Academic Journal of Religious Education)
Der religionspädagogische Diskurs um die Positionalität bzw. Konfessionalität von Religionslehrinnen und Religionslehrern stellt einen zentralen Aspekt professionsbezogener Lehrkräfteforschung dar. Das gilt insbesondere angesichts aktueller konzeptioneller Weiterentwicklungen des konfessionellen Religionsunterrichts sowie eines mehrfach festgestellten schwindenden konfessionellen Bewusstseins bei Lehrkräften. Der vorliegende Beitrag geht dieser Problematik auf Basis einer Befragung von christlichen Religionslehrkräften zu ihrem professionsbezogenen Selbstverständnis nach. Er präsentiert Forschungsfrage, methodische Anlage sowie explorative Befunde einer qualitativen Studie, in der 344 Statements mittels eines induktiven Kategoriensystems inhaltsanalytisch ausgewertet worden sind.
Keywords: Konfessionalität; Religionslehrkräfte; professionelles Selbstverständnis; konfessioneller Religionsunterricht; Lehrerbildungsforschung; Inhaltsanalyse

Das Praxissemester aus der Perspektive von Mentor*innen: Aufgaben der Lernorte und wahrgenommene Veränderungsbedarfe - Caruso, Carina; Goller, Michael (Lehrerbildung auf dem Prüfstand)
Mentor*innen unterstützen Studierende u.a. bei der Planung, Durchführung und Reflexion von Unterricht. Obwohl Mentor*innen ein hoher Einfluss auf die Professionalisierung angehender Lehrkräfte zugeschrieben wird, gibt es nur wenige Studien, in denen die Perspektive von Mentor*innen beforscht wird. Dieser Beitrag zielt darauf, die Perspektive von Mentor*innen zu den Aufgaben der am Praxissemester beteiligten Lernorte sowie Veränderungsbedarfe zu explorieren. Hierzu werden Ergebnisse einer Interviewstudie mit 23 Mentor*innen vorgestellt, die zur Beantwortung nachstehender Forschungsfragen beitragen: (1) Welche Aufgaben haben die am Praxissemester beteiligten Lernorte und die dort tätigen Akteur*innen hinsichtlich der Vorbereitung, Unterstützung und Begleitung der Studierenden im Praxissemester aus Perspektive befragter Mentor*innen? (2) Was sind aus Sicht von Mentor*innen Veränderungsbedarfe hinsichtlich der Rahmenbedingungen bzw. Konzeption des Praxissemesters? Ein zentraler Befund der Studie ist, dass allen Lernorten attribuiert wird, dass diese Studierende auf die praktische Unterrichtstätigkeit vorbereiten sollen. Die Relevanz der Universitäten wird dabei allerdings als gering eingeschätzt. Auch theoretisch-reflexive Aspekte spielen in den Aussagen der meisten Mentor*innen keine Rolle. Veränderungsbedarf wird von den Mentor*innen vor allem in der Rolle des Zentrums für schulpraktische Lehrerausbildung und der Universität gesehen. Diese Befunde werden anschließend kritisch diskutiert.
Keywords: Lehrerbildung; Mentoring; Praxissemester; Professionalisierung / internship; mentoring; professionalisation; teacher education

Theorie und Praxis in der Lehrerbildung

Zur Relevanz von Fallarbeit - Caruso, Carina; Woppowa, Jan (Religionspädagogische Beiträge. Journal for Religion in Education)
Der Beitrag verbindet die Sichtweisen verschiedener Professionalisierungsansätze mit der Frage nach der Gestaltung der (universitären) Begleitung angehender Lehrkräfte im Praxissemester. Dabei wird der Wert von Fallarbeit herausgearbeitet und beschrieben, wie eine Unterstützung angehender (Religions-)Lehrkräfte gestaltet sein müsste, um Entwicklung und Lernen im Praxissemester systematisch zu begleiten. Der Beitrag widmet sich daher zuerst den Rahmenbedingungen und Forschungsbefunden zu Langzeitpraktika und der Gestalt von Professionalisierung durch Praxis. Daran schließen sich Denkfiguren zur Unterstützung (religionspädagogischer) Professionalisierungsprozesse von angehenden Lehrkräften im Schulpraktikum durch rekonstruktive Fallarbeit an, aus Sicht etablierter Professionalisierungsansätze.
Keywords: Fallarbeit; Praxissemester; Professionalität; Professionalisierung; Lehrerinnen- und Lehrerbildung / casework; teacher education; internship; professionalization; professionalism

Aufgaben, Ziele und Betreuungsstrategien von am Praxissemester beteiligten Lehrkräften - Caruso, Carina; Goller, Michael (PraxisForschungLehrer*innenBildung)
Im Praxissemester sind Mentor*innen für Studierende wichtige Bezugspersonen und Kooperationspartner*innen, die die Studierenden u.a. bei der Planung, Durchführung und Reflexion von Unterricht begleiten. Während z.B. zur Kompetenzentwicklung Studierender im Praxissemester mehrere Erkenntnisse vorliegen, wurde die Perspektive von Mentor*innen bisher wenig untersucht. Dieser Beitrag zielt darauf, die Perspektive und Erfahrungen von Mentor*innen zu explorieren und sichtbar zu machen. In diesem Zusammenhang werden Ergebnisse einer leitfadenzentrierten Interviewstudie vorgestellt, an der 23 nordrhein-westfälische Lehrkräfte teilnahmen. Auf Grundlage der inhaltsanalytischen Auswertung der Transkripte werden die nachstehenden Fragestellungen beantwortet: (1) Was sind aus Sicht von Mentor*innen Aufgaben im Zusammenhang mit der Betreuung und Begleitung von Praxissemesterstudierenden? (2) Welche Ziele haben Praxisphasen aus der Perspektive der Mentor*innen? (3) Welchen Betreuungsstrategien folgen Mentor*innen bei der Betreuung und Begleitung von Praxissemesterstudierenden? Die Ergebnisse zeigen, dass die Antworten der Mentor*innen hinsichtlich der ihnen selbst zugeschriebenen Aufgaben und der dem Praxissemester attribuierten Ziele kaum differieren. Die Betreuungsstrategien der Befragten unterscheiden sich hingegen vergleichsweise stark. Unterschiede bestehen u.a. bezüglich der den Studierenden zugesprochenen Freiheitsgrade bei der Unterrichtsplanung und -durchführung sowie bei der (gemeinsamen) Gestaltung der Unterrichtsplanung bzw. -vorbesprechung.
Keywords: Lehrer*innenbildung; Mentoring; Praxissemester; Professionalisierung; Kompetenzentwicklung

Bildungswissenschaftliches Wissen und Kompetenzselbsteinschätzungen unter Berücksichtigung individueller Voraussetzungen - Caruso, Carina; Seifert, Andreas (PraxisForschungLehrer*innenBildung)
m Zentrum dieses Beitrags stehen Ergebnisse der Messung pädagogischer Kompetenzen Studierender, die das Praxissemester absolviert haben. Das bildungswissenschaftliche Wissen, Kompetenzselbsteinschätzungen sowie die Einschätzung der im Praxissemester erreichten Ziele Studierender werden dabei unter Berücksichtigung ihrer individuellen Voraussetzungen (Ausrichtung des Lehramtsstudiums auf eine Schulform; Geschlecht; Alter; Abitur- und Bachelornote) betrachtet (N = 2 008). Bevor die Hypothesen abgeleitet, die Anlage der Studie sowie die Testinstrumente vorgestellt, die Ergebnisse präsentiert und diskutiert werden, stehen u. a. exemplarische Forschungsbefunde zur schulformspezifischen Professionalisierung sowie Annahmen zur Relevanz von Wissen für Lehrerhandeln im Fokus. Die Ergebnisse zeigen u. a. (1) signifikante Mittelwertsunterschiede in den Studiengängen bezüglich des Geschlechts, des Alters, der Abitur- und Bachelornote, (2) dass das Geschlecht, die Abitur- und Bachelornote signifikante Prädiktoren für das bildungswissenschaftliche Wissen sind, (3) dass sich die Kompetenzselbsteinschätzungen insbesondere in Abhängigkeit der Ausrichtung des Lehramtsstudiums auf eine Schulform unterscheiden und (4) dass die Einschätzung der im Praxissemester erreichten Ziele in Abhängigkeit des Geschlechts differiert.
Keywords: Bildungswissenschaftliches Wissen; Hintergrundmerkmale; Kompetenzmessung; Kompetenzselbsteinschätzung; Praxissemester; Professionalisierung

Anomalous bulk diffusion of methylene diphenyl diisocyanate in silicone elastomer - Wortmann, Martin; Viertel, Klaus; Welle, Alexander; Keil, Waldemar; Frese, Natalie; Hachmann, Wiebke; Krieger, Philipp; Brikmann, Johannes; Schmidt, Claudia; Moritzer, Elmar; Hüsgen, Bruno (International Journal of Heat and Mass Transfer)
Keywords: Fluid Flow and Transfer Processes; Mechanical Engineering; Condensed Matter Physics

Fachdidaktische Ansätze der Theorie-Praxis-Relationierung - Caruso, Carina; Harteis, Christian; Gröschner, Alexander (Theorie und Praxis in der Lehrerbildung: Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)
Der Beitrag konstituiert sich als Zusammenschau von Perspektiven der Beiträge, die in diesem Sammelband enthalten sind. Es werden dabei Kerninhalte wie zentrale Fragen, Gestaltungsansätze und Perspektiven der Beiträge gebündelt, wobei die einzelnen fachdidaktischen Akzentuierungen in Bezug auf das Verständnis der Theorie-Praxis-Relationierung sowie fachspezifische Impulse zur Gestaltung der Lernbegleitung nicht wiederholt werden. Vielmehr zielt der Beitrag darauf ab, ausgewählte Aspekte zusammenzuführen und kritisch zu diskutieren, um Akzentuierungen in den fachdidaktischen Perspektiven hervorzuheben. Um diesem Vorhaben Rechnung zu tragen, gliedert sich dieses Resümee entlang der fachspezifischen Besonderheiten und Gemeinsamkeiten, die in den voranstehenden Beiträgen zur Geltung kommen. Im Rahmen einer abschließenden Diskussion werden Fragen hinsichtlich der zukünftigen Theorie-Praxis-Relationierung aufgeführt, deren Beantwortung als Aufgabe der Lehrerbildung bestehen bleibt.
Keywords: Fachdidaktik; Lehrerbildung; Professionalisierung; Theorie-Praxis-Relationierung

(Medienbezogene) Lerngelegenheiten und Kompetenzbedarfe im Vorbereitungsdienst - Caruso, Carina; Bruns, Marike (Das Bildungssystem in Zeiten der Krise Empirische Befunde, Konsequenzen und Potenziale für das Lehren und Lernen)
Lehramtsanwärter*innen können pandemiebedingt häufig weder wie gewohnt bedarfsdeckenden Unterricht noch Ausbildungsunterricht durchführen. Stattdessen konzipieren sie u.a. Lerngelegenheiten für den (digital gestützten) Fernunterricht und den Unterricht unter Berücksichtigung der Hygiene- und Abstandsregeln, sodass sich ihre Tätigkeiten von denen unter regulären Bedingungen unterscheiden. Hinzu absolvieren sie teilweise modifizierte unterrichtspraktische Prüfungen in Form von (digital gestützten) Ersatzleistungen. Anzunehmen ist, dass diese Bedingungen einerseits dazu führen, dass die Anwärter*innen mit Situationen konfrontiert sind, die sie zur Erweiterung ihrer eigenen (Medien-)Kompetenzen nutzen können. Andererseits kann der veränderte Vorbereitungsdienst und der erforderliche Einsatz digitaler Medien Kompetenzbedarfe aufdecken sowie Überforderungen auslösen. Im Zentrum des Beitrags steht eine explorative, leitfadengestützte Interviewstudie mit Lehramtsanwärter*innen. Die Studie zielt darauf, die Rahmenbedingungen näher zu beleuchten, unter denen Lehramtsanwärter*innen im Jahr 2020 ihren Vorbereitungsdienst absolvieren und ihre Erfahrungen zu explorieren.
Keywords: Lehramtsanwärter*innen; Lehrer*innenbildung; Medienkompetenz; Professionalisierung; Vorbereitungsdienst

Praxisphasen in der Lehrerbildung - Caruso, Carina; Harteis, Christian; Gröschner, Alexander (Theorie und Praxis in der Lehrerbildung Verhältnisbestimmungen aus der Perspektive von Fachdidaktiken)
Die Ausweitung schulpraktischer Anteile bzw. die Integration von Langzeitpraktika kennzeichnet die universitäre Lehrerbildung in Deutschland. Mit dieser Ausweitung bzw. Integration ist der Anspruch verbunden, dass schulpraktische Anteile im Studium die professionelle Entwicklung angehender Lehrpersonen positiv beeinflussen.

Eingeprägte Ordnungen in digital gestützte Praktiken im (Religions-)Unterricht - Caruso, Carina; Reis, Oliver (Digitale Praktiken (Jahrbuch für konstruktivistische Religionspädagogik))